2017
DOI: 10.1016/j.neulet.2017.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Establishing between-session reliability of TMS-conditioned soleus H-reflexes

Abstract: Transcranial magnetic stimulation (TMS) of the primary motor cortex (M1) can be used to evaluate descending corticomotor influences on spinal reflex excitability through modulation of the Hoffman reflex (H-reflex). The purpose of this study was to characterize between-session reliability of cortical, spinal, and cortical-conditioned spinal excitability measures collected from the soleus muscle. Thirteen able-bodied young adult participants were tested over four sessions. Intraclass correlation coefficients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(26 citation statements)
references
References 34 publications
2
24
0
Order By: Relevance
“…For example, pairing TMS with peripheral nerve stimulation at varying latencies can elucidate how descending circuits influence the spinally-mediated Hoffman’s reflex (H-reflex) response. TMS-conditioning of the H-reflex has been used to evaluate short-latency facilitation (SLF) and long-latency facilitation (LLF) (Geertsen, van de Ruit, Grey, & Nielsen, 2011; Gray, Sabatier, Kesar, & Borich, 2017). SLF is purported to reflect the strength of fast-conducting monosynaptic descending projections, while LLF evaluates the strength of the indirect, polysynaptic descending projections (e.g.…”
Section: The Use Of Tms For Studying Lower Limb Musculature Presents mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, pairing TMS with peripheral nerve stimulation at varying latencies can elucidate how descending circuits influence the spinally-mediated Hoffman’s reflex (H-reflex) response. TMS-conditioning of the H-reflex has been used to evaluate short-latency facilitation (SLF) and long-latency facilitation (LLF) (Geertsen, van de Ruit, Grey, & Nielsen, 2011; Gray, Sabatier, Kesar, & Borich, 2017). SLF is purported to reflect the strength of fast-conducting monosynaptic descending projections, while LLF evaluates the strength of the indirect, polysynaptic descending projections (e.g.…”
Section: The Use Of Tms For Studying Lower Limb Musculature Presents mentioning
confidence: 99%
“…SLF is purported to reflect the strength of fast-conducting monosynaptic descending projections, while LLF evaluates the strength of the indirect, polysynaptic descending projections (e.g. cortico-reticular, cortico-vestibular) onto the lower motor neuron pool (Geertsen et al, 2011; Gray, Sabatier, et al, 2017). Given the potentially greater role played by polysynaptic descending pathways in LE motor control, measures such as LLF may be particularly valuable for LE studies.…”
Section: The Use Of Tms For Studying Lower Limb Musculature Presents mentioning
confidence: 99%
“…Additionally, the study’s results for MEP amplitude showed high ICC and relatively high typical percentage error, similar to our results. The second study examined only active motor threshold of the right SOL, which had an ICC of 0.95 (Gray, Sabatier, 2017). Though SOL CSP was feasibly measured in our healthy participants as in previous work (Ziemann et al, 1993), our results indicated that SOL CSP might not be as reliable as RMT and latencies.…”
Section: Discussionmentioning
confidence: 99%
“…The reliability (intra-rater, inter-rater, and test-retest) of these measures in neurologically intact adults has been inconsistently examined in the past decade, partly due to the variation in methodology and laboratory set-up. These studies have demonstrated that some SOL (Gray et al, 2017, Lewis et al, 2014) and TA (Cacchio et al, 2009, Chung and Mak, 2015, Forster et al, 2014, Forster et al, 2012, Souron et al, 2016, Tallent et al, 2012, van Hedel et al, 2007) CMC measures can be reliably assessed in healthy adults, including resting and active motor thresholds, amplitude and latency of the motor evoked potential (MEP), and cortical silent period (CSP). Despite the valuable information that these studies have provided to the field, several methodological considerations make compilation of the reliability data difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Short-interval facilitation (SIF) also often referred to as 'short latency facilitation of the H-reflex occurs when a subthreshold TMS pulse is delivered 1-5 ms after a PNS pulse, allowing the direct, fastest descending volley to arrive at the spinal LMN pool prior to the afferent signal, and enhance the H-reflex amplitude by modulating the excitability of the LMN pool (Nielsen and Petersen, 1995b;Gray et al, 2017). Long-interval facilitation (LIF), also referred to as long latency facilitation, occurs when a TMS pulse is delivered before PNS, allowing indirect, slower descending volleys to arrive prior to the afferent signal (Nielsen and Petersen, 1995b;Gray et al, 2017). Thus, SIF and LIF provide measures to non-invasively probe the specific sites and mechanisms of neuromotor circuit connections between cortical and spinal circuitry, which are previously poorly understood.…”
Section: Introductionmentioning
confidence: 99%